2000
DOI: 10.1246/cl.2000.722
|View full text |Cite
|
Sign up to set email alerts
|

HI-Mediated Cyclization of o-Alkynylstyrenes

Abstract: o-Alkynylstyrenes cyclized in the presence of hydroiodic acid to yield polysubstituted iodoindenes. This reaction provides an efficient synthetic method for the preparation of polysubstituted iodoindenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…5 A variety of transition metal complexes, e.g., Pd, 6 Ni, 7 and Co, 8 have been used to synthesize indenes via carboannulations of alkynes, but there are only limited reports for the synthesis of haloindenes, such as the bromination of indane or indene derivatives 9 and hydrogen iodide mediated cyclizations of o-alkynylstyrenes. 10 Roussel et al reported the synthesis of 3-chloroindenes by trifluoromethanesulfonic acid catalyzed benzoylation of 2-methyl-2-butene. 11 Sauers et al reported the synthesis of fluoroindenes by rearrangement of diazirines via photolysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 A variety of transition metal complexes, e.g., Pd, 6 Ni, 7 and Co, 8 have been used to synthesize indenes via carboannulations of alkynes, but there are only limited reports for the synthesis of haloindenes, such as the bromination of indane or indene derivatives 9 and hydrogen iodide mediated cyclizations of o-alkynylstyrenes. 10 Roussel et al reported the synthesis of 3-chloroindenes by trifluoromethanesulfonic acid catalyzed benzoylation of 2-methyl-2-butene. 11 Sauers et al reported the synthesis of fluoroindenes by rearrangement of diazirines via photolysis.…”
mentioning
confidence: 99%
“…Therefore, a number of synthetic approaches toward the construction of indene ring systems have been developed such as the reduction or dehydration of indanone, the cyclization of substituted 1,3-butadienes in the presence of Lewis acids, or the ring expansion of suitably substituted cyclopropenes . A variety of transition metal complexes, e.g., Pd, Ni, and Co, have been used to synthesize indenes via carboannulations of alkynes, but there are only limited reports for the synthesis of haloindenes, such as the bromination of indane or indene derivatives and hydrogen iodide mediated cyclizations of o -alkynylstyrenes . Roussel et al reported the synthesis of 3-chloroindenes by trifluoromethanesulfonic acid catalyzed benzoylation of 2-methyl-2-butene .…”
mentioning
confidence: 99%
“…Indene derivatives, in particular multiply substituted ones, have been attractive, and synthetically useful methods for their synthesis have been developed . Among these known procedures, the most frequently used protocol is to use phenyl-substituted alkenes or phenyl-substituted allyl alcohols. The cycloalkylation process of the phenyl-substituted alkenes results in the formation of indene derivatives, for example, via the photo or thermo rearrangement of 3-arylcyclopropenes 2,3 or via the cyclization of phenylvinyl derivatives. o -Alkynylstyrenes underwent HI-mediated cyclization to form iodoindene derivatives . When treated with acids, the phenyl-substituted allyl alcohols afford phenyl-substituted allyl cations, which undergo electrocyclic ring closure to form indene derivatives by the elimination of a proton. …”
Section: Introductionmentioning
confidence: 99%
“…This structural unit also serves as building blocks for the synthesis of optoelectronic devices in material sciences and as ligand precursors in homogeneous catalysis . Considering the interest for this scaffold and the need for synthetic methodologies enabling the introduction of substituent diversity upon postfunctionalization, some effort has been devoted to the synthesis of 2- and 3-haloindenes. Among the various routes developed, the strategies based on the electrophilic activation of a C–C unsaturation followed by the intramolecular attack of a carbon nucleophile play a pivotal role as they allow the formation of complex, polysubstituted structures from simple precursors in one step using an efficient and atom-economical protocol . So far, much attention has been paid to methodologies involving the activation of an alkyne function either in the presence of protic or halogen electrophiles delivering the 3-iodoindene isomer.…”
mentioning
confidence: 99%
“…Considering the interest for this scaffold and the need for synthetic methodologies enabling the introduction of substituent diversity upon postfunctionalization, some effort has been devoted to the synthesis of 2- and 3-haloindenes. Among the various routes developed, the strategies based on the electrophilic activation of a C–C unsaturation followed by the intramolecular attack of a carbon nucleophile play a pivotal role as they allow the formation of complex, polysubstituted structures from simple precursors in one step using an efficient and atom-economical protocol . So far, much attention has been paid to methodologies involving the activation of an alkyne function either in the presence of protic or halogen electrophiles delivering the 3-iodoindene isomer. More recently, methodologies involving iodonium-induced activation of propargylic alcohol substrates have offered the opportunity to synthesize functionalized 2-iodoindenyl products via a tandem reaction in the presence of a second nucleophile (Scheme , eq 1).…”
mentioning
confidence: 99%